2020
DOI: 10.1155/2020/6630546
|View full text |Cite
|
Sign up to set email alerts
|

Research on the Large Deformation Prediction Model and Supporting Measures of Soft Rock Tunnel

Abstract: The weak surrounding rock has the characteristics of easy softening, poor integrity, low mechanical strength, etc., which makes it easy to induce different degrees of deformation and damage under excavation disturbance and then seriously affects the stability of the tunnel. Carrying out soft rock tunnel deformation prediction research and designing the supporting structure according to the predicted value is of great significance to engineering construction and design. Based on the grey theory, the large defor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1
1

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 11 publications
0
3
0
Order By: Relevance
“…The presence of soft rock such as sandstone and limestone is the main reason for large deformations in the tunnel. Rao et al [28] conducted a deformation study of soft rock based on the gray prediction method, and the control of different support schemes was analyzed by numerical simulation.…”
Section: Applicability Of the Strength Criterionmentioning
confidence: 99%
“…The presence of soft rock such as sandstone and limestone is the main reason for large deformations in the tunnel. Rao et al [28] conducted a deformation study of soft rock based on the gray prediction method, and the control of different support schemes was analyzed by numerical simulation.…”
Section: Applicability Of the Strength Criterionmentioning
confidence: 99%
“…3 In the field of tunnelling, many studies on karst have been reported [4][5][6] ; Tao 7 discovered that dolomite contains CaO, MgO, Al 2 O 3 and other substances. Xie and Rao et al 8,9 conducted an experimental study on the composition of dolomite and found that the main component of dolomite is CaCO 3 and contains MgO and Al 2 O 3 , which have a great influence on the physical properties of dolomite. However, these substances can easily form crystals in the tunnel drains.…”
Section: Introductionmentioning
confidence: 99%
“…The dolomite area often presents karst caves after being eroded by water, which belongs to special unfavorable geology. In the field of tunnel engineering, there have been many literatures on the research on karst caves [2,3] ; Yee et al [4] analyzed the pipeline fouling and found that it contains aragonite and calcite, and the degradation of aragonite and calcite is beneficial to relieve pipeline blockage. In the research of crystal plugging factors.…”
Section: Introductionmentioning
confidence: 99%